2018
DOI: 10.1186/s12917-018-1547-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of acute canine leptospirosis using multiple laboratory tests and characterization of the isolated strains

Abstract: BackgroundDogs presenting with acute leptospirosis may present non-specific clinical and laboratory findings, and the definitive diagnosis may require additional confirmatory tests, including bacterial culture, for the direct or indirect identification of the pathogen. The present study describes the diagnosis of leptospirosis in suspected dogs based on the use of multiple diagnostic tests, including serological, molecular and bacteriological tests, along with the characterization of the recovered leptospiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 38 publications
(51 reference statements)
7
42
0
1
Order By: Relevance
“…Comparatively similar, L. kirshneri was detected in all sample types except in liver. The detection of L. interrogans and L. kirshneri were expected in this study and both species had been commonly associated with canine leptospirosis [1,31,39,40]. However, the detection of L. borgpetersenii was linked to contacts with rats as this bacterium is commonly shed by rats [28,41,42].…”
Section: Discussionsupporting
confidence: 48%
“…Comparatively similar, L. kirshneri was detected in all sample types except in liver. The detection of L. interrogans and L. kirshneri were expected in this study and both species had been commonly associated with canine leptospirosis [1,31,39,40]. However, the detection of L. borgpetersenii was linked to contacts with rats as this bacterium is commonly shed by rats [28,41,42].…”
Section: Discussionsupporting
confidence: 48%
“…Martin et al (28) and Miotto et al (29) found that antibody titers against Leptospira spp. were often negative during the clinical phase of the disease and, at best, the titers ranged between 100 and 200 six months after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, smaller doses were not attempted. In addition, it was thought that a relatively long treatment scheme was necessary given the zoonotic nature of the disease and to avoid the possibility of ending up with a patient suffering from chronic leptospirosis (29). Also, it is important to mention that the referred Monte-Carlo simulations were derived from PK data generated in healthy dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting, ST (7LBoonsilp) 17 isolates were responsible for an outbreak of severe leptospirosis among capuchin monkeys in a Colombian wildlife rehabilitation centre (Szonyi, Agudelo‐Florez, Ramirez, Moreno, & Ko, ). More recently, Miotto et al () described ST (7LBoonsilp) 17 in dogs, in São Paulo, Brazil. This study hence provides novel data on globally widespread (and maybe more virulent) Leptospira genotypes circulating in Portugal, specifically on the L. interrogans ST (7LBoonsilp) 17 isolates.…”
Section: Discussionmentioning
confidence: 99%